The death and afterlife of Mahatma Gandhi - Paranjape, Makarand R. (Routledge Hindu studies series, 2014)
"Who is responsible for the Mahatma's death? Just one single fanatic, the whole ideology of Hindu nationalism, the ruling Congress-led Government who failed to protect him, or a vast majority of Indians and their descendants who considered Gandhi irrelevant? Such questions mean that Gandhi, even after his tragic and brutal death, continued to haunt India - perhaps more effectively in his afterlife than when he lived. The Death and Afterlife of Mahatma Gandhi is a ground-breaking and profound analysis of the assassination of the "father of the nation" and its after-effects. Paranjape argues that such a catastrophic event during the very birth pangs of a new nation placed a huge burden of Oedipal guilt on India, and that this is the reason for the massive repression of the murder in India's political psyche. The enduring influence of Gandhi is analysed, including the spectral presence of his portrayal in Indian cinema. The book culminates in Paranjape's reading of Gandhi's last six months in Delhi, where from the very edge of the grave he wrought what was perhaps his greatest miracle, the saving of Delhi and thus of India itself from internecine bloodshed. This evocative and moving meditation into the meaning of the Mahatma's death will be relevant to scholars of Political and Cultural History in India, as well as those with an interest in studies on Gandhi"--